Compensation for Oil Pollution Due to Tanker Accidents in the Indonesian Legal System in a Justice Value Perspective - Gede Sudika Mangku, Dewa; Kristianti Purwendah, Elly; Rantau Itasari, Endah; Resti Nurhayati, Bernadeta (International Journal of Criminology and Sociology, 2022)
The sea potentially fulfills the interests of sea transportation; for example, the transportation of tankers. The Indonesian sea is included in the seas with the dense traffic of tankers causing the risk of oil pollution due to tanker accidents. For example, the three cases of oil contamination caused by tanker accidents occurred in the Cilacap Sea which is the largest oil refinery in Indonesia. This study aimed to find the value of justice for oil pollution losses due to tanker accidents considering that Indonesia has ratified the international convention of the civil liability of oil spill by tanker, Convention on Civil Liability 1969, and its amendment of Convention on Civil Liability 1992, along with its supplementary protocol. The international law principles (polluter pays principle, precautionary principle, and strict liability) for oil tanker losses caused by tankers have been applied to the national legal system. There were still overlapping authorities and the conflicts of authorities among the institutes in the period before 2015 before the establishment of the Coordinating Ministry of Marine Affairs. After the periodization of 2015 with the formation of the Coordinating Ministry of Marine Affairs, it is expected to resolve the loss of oil pollution as a result of tanker accidents using the right method of calculating the loss of natural resources, taking into account the willingness to pay and the willingness to accept between the insurance and victims.